Railway fastening clips dataset wth fastclip - Shallari, Irida (Mid Sweden University, 2022)
Railway fastening clips dataset wth fastclip.

This record contains a dataset with the railway fastening clip called fastclip and the installation datasheet for the same clip provided by the clip manufacturer, Pandrol AB.

The railway_dataset folder contains three subfolders:
- The calibration folder, where are the images taken at angles from 0–30 with a step of 3 degrees.
- The test and the validation folder, where are the images and their respective labels based on the YOLO Oriented Bounding Box method.
The fastclip datasheet document is an installation sheet provided from the manufacturer of the fastclip, Pandrol AB.


The dataset was originally published in DiVA and moved to SND in 2024.
Railway fastening clips dataset wth fastclip
Keywords: railway transport; järnvägstransport; railway tracks; rälsar; Engineering and Technology; Teknik; Embedded Systems; Inbäddad systemteknik